2010
DOI: 10.1016/j.jwb.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Managing FDI technology spillovers: A challenge to TNCs in emerging markets

Abstract: Prior studies on FDI technology spillovers have offered little guidance to TNCs on how to protect and exploit technology across borders. The present paper argues that TNCs can manage technology spillovers through selection of entry modes, selection of technologies, and selection of investment priorities in the affiliates they establish in foreign markets. A number of hypotheses are derived from theoretical analyses and are tested against firm-level data from China. The findings of the paper have significant im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Along this line, Takii () suggests that majority‐foreign plants are more effective in preventing the diffusion of proprietary knowledge in the local economy, and demonstrates that industries characterized by a strong presence of majority foreign‐owned affiliates originate lower spillovers. Similarly, Tian () finds that FDI‐KSs are more likely to happen in joint ventures rather than wholly owned subsidiaries.…”
Section: Antecedents Of Fdi Knowledge Spilloversmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this line, Takii () suggests that majority‐foreign plants are more effective in preventing the diffusion of proprietary knowledge in the local economy, and demonstrates that industries characterized by a strong presence of majority foreign‐owned affiliates originate lower spillovers. Similarly, Tian () finds that FDI‐KSs are more likely to happen in joint ventures rather than wholly owned subsidiaries.…”
Section: Antecedents Of Fdi Knowledge Spilloversmentioning
confidence: 99%
“…In this view, subsidiaries can strategically manage their knowledge in the host country, thus generating different levels of KSs. Accordingly, recent empirical research has started to analyse subsidiary knowledge protection strategies (de Faria and Sofka ; Tian ). This literature suggests that subsidiaries consider host country firms as the source of knowledge appropriation risks, thus actively selecting a combination of formal and strategic protection tools (de Faria and Sofka ).…”
Section: Antecedents Of Fdi Knowledge Spilloversmentioning
confidence: 99%
“…In this paper we hypothesize that there is an explicit positive association between TNCs' local purchasing from domestic suppliers and technological cooperative relationships between TNCs and domestic firms. Domestic client linkages Studies have found that domestic client linkages are likely to produce more opportunities for domestic firms to cooperate with TNCs and trigger more spillover from TNCs (Tian, 2010). Sun and Du (2011) summarized that, through the client and forward linkages between TNCs and domestic firms, foreign finns can teach domestic firms how to run and maintain the equipment, and domestic firms would also receive knowledge from foreign partners by using their products and equipment.…”
Section: Tncs' Technology Linkages: Key Explanatory Variables and Hypmentioning
confidence: 99%
“…WOS have positive spillovers with total sales and fixed assets measures, and MAJVs have positive spillover effects in all three measures. The findings of positive spillovers from MAJVs are consistent with Abraham et al (2010) and Tian (2010). However, in contrast to findings of negative effects from WOS in Javorcik and Spatareanu (2008) and Abraham et al (2010), this study finds that WOS are also associated with positive spillover effects.…”
Section: Model Estimationsupporting
confidence: 57%